ANALISIS KEPUASAN MAHASISWA TERHADAP KUALITAS PEMBELAJARAN MENGGUNAKAN INTEGRASI MODEL KANO DAN QUALITY FUNCTION DEPLOYMENT (QFD) - Fitri Romaito Lubis; Martua Siregar (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze student satisfaction with the quality of learning services and to determine priority strategies for improving the learning process in higher education using an integrated Kano Model and Quality Function Deployment (QFD) approach. Methods: This research employed a quantitative descriptive method with data collected through questionnaires distributed to students. The attributes of learning services were analyzed using the Kano Model to classify service characteristics based on their influence on student satisfaction. Furthermore, Quality Function Deployment (QFD) was applied through the House of Quality (HoQ) matrix to translate student needs into technical improvement strategies. Results: The results show that all learning service attributes fall into the One-Dimensional category, indicating that improvements in these attributes directly increase student satisfaction. The priority attributes include teaching competence, learning strategies, learning facilities, and accessibility of online academic information. Novelty: This study provides a comprehensive model for improving the quality of higher education learning services through the integration of Voice of Customer, Kano Model, and QFD, which enables universities to systematically identify student needs and translate them into strategic improvements.